Teorias sociológicas sobre a modernidade e práticas civilizatórias contemporâneas - Leal, Edilene Maria de Carvalho (2013)
The aim of this thesis is to analyze the effective possibilities of civilizing practices in the contemporary societies. For this, two fundamental hypotheses guided, so surreptitious but emphatic, the arguments of this analysis: the first would be the denial of the modern belief in the broad and inexorable powers of the rationality . both the rationality which pointed to their universally positive results, as that which was a scathing criticism of its inability to produce a civilly shared world; the second refers to the denial of a postmodern critical deconstruction of rationality, which resulted in the world of the relativism and the consequent configuration of the world without ethical appreciation. On occasion, we analyze the metaphysics that animated the modernity: the tireless attempt to separate the rationality from the negative influence of the irrationality data. However, not all thinkers surrendered to the rationalist project of the modernity. Freud, Arendt, Foucault, for example, realized that the combination of various disparate elements: it.s, simultaneously, rational and irrational; factual and evaluative; regular and contingent. It was these and other important authors who helped us to think about the second working hypothesis of this thesis, namely, that meaning of the terms modernity and civilization, as well as all the other terms relating to them, are constructed in their daily use, social practices, the collective shocks and political struggles. Thus, there is no meanings that precede their subscriptions in the world, i.e. the world is the result of the effect of each thing, each object, each process. With this, we are not saying that particular meaning of civilization cannot remain active in the orientation of collective conduct (of societies), as if we were denying the possibility of creating lasting consensus. We are not positioned in favor of the relativism; to the contrary, we have argued that, even in contemporary societies, can be viewed attempts to develop productive practices civilizing. Finally, what articulate such hypotheses is the understanding that the practices of any kind are studded end to end by relations of power, relation of force and interests, which provide the tone and texture of the scientific, social, political and cultural dynamics, which characterize, deeply, the development of the civilizing action.